Lessons Learned for Establishing Hospital Safety Climate with ROI vs Cost Control Approach as a Budget Policy Advocacy - Nurani, Promisetyaningrum Fitria; Siregar, M Arbi; N, Pramadyo Adhi; H, Ria Nuril (PubHealth Jurnal Kesehatan Masyarakat, 2025)
Objective: The classical issue in most of the Asian countries on establishing hospital safety climate is the lack of budget for safety program due to the management perspective that safety is a burden. It makes safety programs annually only submitted but unapproved because of various management decisions allocating the budget to another program which is considered to be more important. With a lack of budget makes many safety programs are stuck and unimproved. Activity: In the field visit from one of the famous referral hospitals in Yogyakarta, hospital safety climate implementation is reviewed as a picture of hospital safety climate in general. This paper tries to solve the classical issue that inhibits the safety climate implementation in the hospital with a brief introduction to the ROI vs Cost Control for the decision-makers which referenced from various journals as the evidence. Regulation Review: The laws and regulations regarding hospital safety have entered into the legal system that must be fulfilled by the hospital through accreditation at least once every 3 years. However, some of the hospital safety implementations as a major part of the safety climate in hospital runs into unsustain because it is only done as a fulfillment of the obligation to pass accreditation completely which is called "SNARS" (Standar Nasional Akreditasi Rumah Sakit). Even though the rules regarding hospital safety should be used as a reference for establishing a sustainable hospital safety climate but in facts it is not well implemented. Lessons Learned: Safety paradigm will change among the decision-makers from the perspective of safety as a burden and fulfilment of accreditation requirements to the perspective of safety as an investment that can provide long-term benefits for hospitals by calculating ROI vs Cost Control for all safety program and its infrastructure. However, it is very important to establish safety climate in the hospital.ROI vs Cost Control calculations are the main tool for making a paradigm shift from viewing K3 as a cost center to a profit center that can provide long-term competitive advantages.